2015
DOI: 10.1074/jbc.m115.691592
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter Activity Is Modulated by α-Synuclein

Abstract: Background: DAT regulates dopamine neurotransmission in the brain. Results: ␣-Synuclein influences DA efflux and membrane microdomain distribution of DAT. Conclusion: DAT activation recruits ␣-synuclein to the membrane, which in turn influences dopamine neurotransmission. Significance: Understanding the mechanisms associated with ␣-synuclein regulation of DAT may reveal disease-modifying targets for the treatment of pathologies associated with DA dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 64 publications
4
78
0
3
Order By: Relevance
“…Therefore, the alpha-synuclein mediated decrease in dopamine uptake alone, might not be the sole underlying mechanism for the elevated extracellular dopamine levels. In a recent study, Butler et al have shown alpha-synuclein overexpression increases the DAT-mediated, nomifensine-sensitive basal dopamine efflux at resting membrane potential [18]. These reports are in agreement with the emerging consensus that alpha-synuclein regulates dopamine neurotransmission by influencing the action potential independent dopamine release via DAT.…”
Section: Alpha-synuclein Regulation Of Dopamine Synthesis Storage Csupporting
confidence: 73%
See 4 more Smart Citations
“…Therefore, the alpha-synuclein mediated decrease in dopamine uptake alone, might not be the sole underlying mechanism for the elevated extracellular dopamine levels. In a recent study, Butler et al have shown alpha-synuclein overexpression increases the DAT-mediated, nomifensine-sensitive basal dopamine efflux at resting membrane potential [18]. These reports are in agreement with the emerging consensus that alpha-synuclein regulates dopamine neurotransmission by influencing the action potential independent dopamine release via DAT.…”
Section: Alpha-synuclein Regulation Of Dopamine Synthesis Storage Csupporting
confidence: 73%
“…A recent study by Ronzitti et al suggests that elevation of extracellular monomeric form of alpha-synuclein mediates Ca 2+ increase via the Cav2.2 N-type Ca 2+ channel in cortical neurons [71], confirming Adamczyk’s report [68]. The alpha-synuclein regulation of Ca 2+ channels in striatal slices has been shown to stimulate dopamine release, potentially via both classical neurotransmission mechanism and efflux of dopamine via DAT [18, 71]. Ronzitti et al postulated that dysregulation of lipid rafts by alpha-synuclein overexpression causes a shift in Cav2.2 channels from cholesterol rich to cholesterol poor membrane microdomains thus altering Cav2.2 function as well as dopamine release.…”
Section: Ca2+ Signalingmentioning
confidence: 67%
See 3 more Smart Citations